The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1159/000101467
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Level in Severe Stenosis of Cerebral Arteries

Abstract: Background: C-reactive protein (CRP) as a non-specific inflammatory biomarker has been demonstrated to actively contribute to all stages of atherogenesis. The aim of this study was to investigate the relation between CRP concentrations and the severity of stenosis of cerebral arteries. Methods: Lipid parameters and CRP levels were measured in the sera of 119 patients with stenosis of the extracranial cerebral arteries established by angiography and compared with the control group, with a normal appearance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…To search for a less invasive and cheaper method to detect ICAO, inflammatory factors such as high-sensitivity C-reactive protein (hs-CRP) have been established in several prospective studies [ 10 12 ]. High-sensitivity CRP is a very sensitive non-specific biomarker contributing to all stages of atherosclerosis [ 10 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To search for a less invasive and cheaper method to detect ICAO, inflammatory factors such as high-sensitivity C-reactive protein (hs-CRP) have been established in several prospective studies [ 10 12 ]. High-sensitivity CRP is a very sensitive non-specific biomarker contributing to all stages of atherosclerosis [ 10 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that the immune system plays a critical role at every stage of the atherosclerotic process, and recently atherosclerosis has been considered to be an essentially inflammatory phenomenon [1]. Oxidation of lipoproteins, as a result of chronic inflammation and immune response, plays a key role in the initiation and progression of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in another study hsCRP concentration was significantly associated with cerebral arteries stenosis >70% [60]. Mullenix PS et al recently showed that hsCRP levels were independently associated with carotid stenosis (odds ratio [OR] 1.2, 95% CI 1.1-1.5, p=0.04), while LDL cholesterol levels were not (OR 1.0, 95% CI 0.98-1.01, p=0.8) [61].…”
Section: The Role Of Hscrp In Ischemic Strokementioning
confidence: 84%